Визначення економічної ефективності роботи комбінованої електростанції з ВДЕ та установкою зберігання енергії - Buratynskyi, Ihor (General Energy Institute of the National Academy of Sciences of Ukraine, 2025)
The introduction of a mechanism for cable connection at one point of two or more power plants that generate electricity from different primary energy sources and energy storage systems is aimed at creating multi-purpose energy parks, in particular, to increase the efficiency of the use of network infrastructure and increase the stability of electricity supply to consumers. In the conditions of operation on electricity market in Ukraine, an assessment of the economic efficiency of the operation of a combined power plant, which includes a wind, solar, maneuverable power plant with an installed capacity of 4 MW each and a two-hour energy storage system with a nominal capacity of 4 MW and a nominal capacity of about 11 MWh, was carried out and the results obtained were compared with the results obtained during the operation of such power plants and energy storage system located at separate sites. It was determined that the construction of a combined power plant allows reducing capital investment costs during the implementation of power plants by 5.1 % by reducing the costs of connection to electrical networks; reduce the levelized cost of energy throughout the entire life cycle by 27.8 % due to an increase in electricity generation volumes relative to a unit of installed capacity, which increases the capacity factor; increase the net present value by 15.3 %, taking into account discounted costs and revenues; reduce the discounted payback period of investments by 12.0 %, in contrast to power plants and energy storage system located on separate sites.